A web based expert system for pre-diagnosing gestational diabetes / Ahlam Zaini Ab Rahim - Ahlam Zaini, Ab Rahim (2006)
Medical area has a lot of contribution in revealing any particulars about the medicine such as type of disease, implication of a disease and also some prediction of having a disease. This research uses rule^based expert system representation and techniques to solve and make a pre-diagnosis of having gestational diabetes (GD) among pregnant women. After several times taken in understanding the domain subject, the researcher listed a set of risk factors and common symptoms, conducted some interviews with some experts in order to get the solution of handling GD and uncertainty management through web-based expert system. Each phase of the research methodology was gone through in order to have and analyze the effectiveness of pre-diagnosing through the web based application.